2020
DOI: 10.1097/nmc.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Sleep Quality in Minority Pregnant Women

Abstract: Purpose: To examine if vitamin D deficiency was associated with poor sleep quality in a sample of African American and Hispanic pregnant women. We also examined if race moderates the relationship between serum 25(OH)D levels and sleep quality among participants in this sample. Study Design and Methods: Using a cross-sectional design, a sample of 115 African American and Hispanic pregnant women were enrolled from a federally qualified health center in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…There are few published studies on the association between poor sleep quality and serum vitamin D levels in the general population [37,[59][60][61]. To date, there have been only four studies investigating the correlation between serum vitamin D levels and sleep quality during pregnancy, but the measurements were restricted to only one time point, providing no insight into changes throughout pregnancy [33,38,40]. In a cross-sectional study by Cheng et al involving 890 Singaporean pregnant women in their second trimester (26-28 weeks), plasma 25(OH)D deficiency was found to be associated with a three-fold increase in the chance of poor sleep quality (PSQI greater than 5), (OR, 3.49; 95% CI, 1.84-6.63) [33].…”
Section: Low Vitamin D Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few published studies on the association between poor sleep quality and serum vitamin D levels in the general population [37,[59][60][61]. To date, there have been only four studies investigating the correlation between serum vitamin D levels and sleep quality during pregnancy, but the measurements were restricted to only one time point, providing no insight into changes throughout pregnancy [33,38,40]. In a cross-sectional study by Cheng et al involving 890 Singaporean pregnant women in their second trimester (26-28 weeks), plasma 25(OH)D deficiency was found to be associated with a three-fold increase in the chance of poor sleep quality (PSQI greater than 5), (OR, 3.49; 95% CI, 1.84-6.63) [33].…”
Section: Low Vitamin D Levelsmentioning
confidence: 99%
“…A recent meta-analysis, in which two of the nine included studies examined pregnant women, found that vitamin D deficiency was associated with a 1.5-times increased chance of women experiencing poor sleep quality, short sleep duration, and sleepiness [37]. To our knowledge, limited studies have evaluated the association between vitamin D levels and sleep patterns in a pregnant population [33,[38][39][40]. Such studies were conducted in the second or third trimester and did not provide insights into the presence or type of sleep disturbances in early pregnancy, nor did they evaluate changes in sleep patterns throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Physical symptoms such as fatigue, poor sleep quality, musculoskeletal pains, and urinary incontinence are more common during pregnancy due to the physiological changes of the body [ 4 ]. These symptoms have also been associated with vitamin D deficiency [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study with pregnant women ( n = 292) and non-pregnant women healthy controls ( n = 200), the researchers found that the risk of poor sleep increased more than two-fold in the second trimester which also correlated with poor quality of life [ 15 ]. Most recently, it was reported that vitamin D may be a significant predictor of poor sleep quality in pregnant women [ 8 ]. A study with 115 pregnant African American and Hispanic women (24–32 weeks gestation) found that lower serum 25(OH)D levels were significantly associated with worse sleep quality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation